'Personality in Its Natural Habitat' Revisited: A Pooled, Multi‐sample Examination of the Relationships Between the Big Five Personality Traits and Daily Behaviour and Language Use. Issue 5 (16th July 2020) - Tackman, Allison M.; Baranski, Erica N.; Danvers, Alexander F.; Sbarra, David A.; Raison, Charles L.; Moseley, Suzanne A.; Polsinelli, Angelina J.; Mehl, Matthias R.
Abstract: Past research using the Electronically Activated Recorder (EAR), an observational ambulatory assessment method for the real‐world measurement of daily behaviour, has identified several behavioural manifestations of the Big Five domains in a small college sample ( N = 96). With the use of a larger and more diverse sample of pooled data from N = 462 participants from a total of four community samples who wore the EAR from 2 to 6 days, the primary purpose of the present study was to obtain more precise and generalizable effect estimates of the Big Five–behaviour relationships and to re‐examine the degree to which these relationships are gender specific. In an extension of the original article, the secondary purpose of the present study was to examine if the Big Five–behaviour relationships differed across two facets of each Big Five domain. Overall, while several of the behavioural manifestations of the Big Five were generally consistent with the trait definitions (replicating some findings from the original article), we found little evidence of gender differences (not replicating a basic finding from the original article). Unique to the present study, the Big Five–behaviour relationships were not always comparable across the two facets of each Big Five domain. © 2020 European Association of Personality Psychology